2022
DOI: 10.1186/s12941-022-00502-w
|View full text |Cite
|
Sign up to set email alerts
|

VIM-encoding IncpSTY plasmids and chromosome-borne integrative and mobilizable elements (IMEs) and integrative and conjugative elements (ICEs) in Pseudomonas

Abstract: Background The carbapenem-resistance genes blaVIM are widely disseminated in Pseudomonas, and frequently harbored within class 1 integrons that reside within various mobile genetic elements (MGEs). However, there are few reports on detailed genetic dissection of blaVIM-carrying MGEs in Pseudomonas. Methods This study presented the complete sequences of five blaVIM-2/-4-carrying MGEs, including two plasmids, two chromosomal integrative and mobilizab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The use of the classical approach to classify Pseudomonas plasmids by the type of their replicon proteins fails to separate two subgroups of the plasmids, containing or lacking the conjugation genes. Earlier, we found the same problem during the study of Acinetobacter plasmids [17]. The use of a complex approach in the classification of plasmids related to pPPUT-Tik1-1 made it possible to reliably determine the boundaries of the pPPUT-Tik1-1 group and separate the two subgroups of these plasmids.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The use of the classical approach to classify Pseudomonas plasmids by the type of their replicon proteins fails to separate two subgroups of the plasmids, containing or lacking the conjugation genes. Earlier, we found the same problem during the study of Acinetobacter plasmids [17]. The use of a complex approach in the classification of plasmids related to pPPUT-Tik1-1 made it possible to reliably determine the boundaries of the pPPUT-Tik1-1 group and separate the two subgroups of these plasmids.…”
Section: Discussionmentioning
confidence: 64%
“…To improve the plasmid classification, two main methods have been developed later, i.e., typing for the replication initiation genes and typing for the relaxation (MOB genes, encoding the conjugative complex) genes [8,[13][14][15][16][17]. While replicon typing aims at plasmid replication regions with non-degenerate primers, MOB typing classifies plasmids into relaxase subfamilies using degenerate primers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our conjugal transfer experiment confirms the Inc pPA7790 plasmid pNY13932-OXA can to transfer between cells. Furthermore, the horizontal transferability of Tn6417-related ICEs and Inc p60512−IMP plasmids was demonstrated in our previous studies [42,59,60]. Of note, Inc p60512−IMP plasmids are transferred through electroporation rather than conjugation because they contain only four conjugal transfer genes (traA, traC, traD and cpl), which is insufficient for plasmid conjugation [43,61].…”
Section: Discussionmentioning
confidence: 84%
“…13 IMEs typically utilize conjugation mechanisms encoded by other MGEs to achieve transfer and integration 14 while ICEs mainly use tyrosine/serine recombinases or DDE transposases for chromosomal integration and excision. 15 In previous study, a number of novel MGEs were identified in P. aeruginosa in China, such as the novel Inc groups: Inc p60512−IMP and Inc pPA7790 ; 16 Tn6852-related IMEs carrying bla PER-1 and bla CARB-2 : Tn6853; 17 Tn6417-related ICEs carrying bla VIM-1 : Tn6953; 18 and Multiple Tn1403-related transposons carrying different class 1 integrons: Tn6847, Tn6849, Tn7454, Tn7484, etc. 16,17,19 Multiple types of novel MGEs are frequently identified in China, which pose unknown challenges to the containment of bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%